2018
DOI: 10.5530/pj.2018.4.138
|View full text |Cite
|
Sign up to set email alerts
|

Immunoinformatics Study of Procyanidins as Mast Cell Stabilizers

Abstract: Background:Allergens are foreign proteins that stimulate the production of immunoglobulin E (IgE), when they come in contact with human body. These allergens after binding with IgE through FcεRI receptor, triggers the signal transduction reaction in mast cell and basophil cells, leading to allergic reactions by releasing some mediators. Mast cell stabilizer block mast cell degranulation, stabilizing the cell and thereby preventing the release of histamine 8 and related mediators e.g. leukotrienes (for basophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Essentially, based on the outcome of recent pre-clinical studies, some active agents have been recognized that have preventive potential against animal models of IPF along with interesting facts related to ability to alter mast cell degranulation via different mechanisms. These antifibrotic agents included adenylyl cyclase activators, β-adenoreceptor agonists, flavonoids, mast cell stabilizers, phosphodiesterase inhibitors and procyanidins [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] . The antifibrotic actions of these agents have been reported at initial and pre-clinical stages as discussed below.…”
Section: Antifibrotic Agents With Mast Cell Stabilization Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Essentially, based on the outcome of recent pre-clinical studies, some active agents have been recognized that have preventive potential against animal models of IPF along with interesting facts related to ability to alter mast cell degranulation via different mechanisms. These antifibrotic agents included adenylyl cyclase activators, β-adenoreceptor agonists, flavonoids, mast cell stabilizers, phosphodiesterase inhibitors and procyanidins [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] . The antifibrotic actions of these agents have been reported at initial and pre-clinical stages as discussed below.…”
Section: Antifibrotic Agents With Mast Cell Stabilization Propertiesmentioning
confidence: 99%
“…Chemically, these are oligomeric flavonoids and oligomers of catechin, epicatechin and their gallic acid esters. Recently, procyanidin C1 type has been identified as natural antiallergic agent, which has possibility to stabilize mast cell during allergic reaction by altering the binding affinity of IgE with FcεRI receptor [68] . In vivo study of proanthocyanidin indicated that, it could inhibit inflammatory cell infiltrations and fibrosis as well as decrease hydroxyproline content [69] .…”
Section: Procyanidinsmentioning
confidence: 99%
“…To prevent the type I hypersensitivity reaction, drugs known as mast cell stabilizers e.g., synthetic, semi synthetic and natural stabilizers, can be used as therapeutic agents. These mast cell stabilizers obtained from natural resources can be classified into different groups such as flavonoids, coumarins, phenols [12], terpenoids, alkaloids etc. Considering their mechanisms of action, mast cell stabilizers can be classified as Ca 2+ channel blocking agents, suppressors of gene expression of genes (tumor necrosis factor alpha, different interleukins), inhibitors for phosphorylation reactions in MAPK, ERK, JNK Gab2 signaling pathways, down regulators of enzyme histidine dicarboxylase, suppressors of mRNA of CD23, inhibitors of COX2/5 lipooxygenase enzyme, inhibitors of prostaglandin D 2 synthesis, LTC 4 inhibitors, and Spleen tyrosin kinase enzyme inhibitors [13].…”
Section: Introductionmentioning
confidence: 99%